2004
DOI: 10.1590/s0021-75572004000200010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico de sobrepeso e obesidade em escolares: utilização do índice de massa corporal segundo padrão internacional

Abstract: Objective: To evaluate the agreement between the body mass index international standard and body fat for the diagnosis of overweight and obesity in schoolchildren.Methods: 528 schoolchildren between 6 and 10 years of age, of both sexes, had their weight and height measured. They were then classified as normal, underweight, overweight or obese using the body fat index for age. Body fat was estimated based on the sum of triceps and subscapular, triceps and calf skinfold measurements and waist and hip circumferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
1
33

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 17 publications
4
21
1
33
Order By: Relevance
“…At A3, O/O was observed in 53.9% of the studied individuals, and in the same population, an increased in the prevalence of overweight along the years was observed, which confirms other studies' results [11][12][13] . Another important finding was that Group O/O since childhood and adolescence presented higher mean values of BP and higher percentage of individuals with increased BP in all the assessments.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At A3, O/O was observed in 53.9% of the studied individuals, and in the same population, an increased in the prevalence of overweight along the years was observed, which confirms other studies' results [11][12][13] . Another important finding was that Group O/O since childhood and adolescence presented higher mean values of BP and higher percentage of individuals with increased BP in all the assessments.…”
Section: Discussionsupporting
confidence: 89%
“…In this context, we highlight the Bogalusa study that, based on many cohorts, demonstrated that cardiovascular risk factors are present since the childhood/adolescence (C/A) 7 and have a relation to atherosclerotic lesions evidenced in studies of necropsy in young individuals [8][9][10] . Data on overweight/obesity (O/O) in Brazilian population reinforce its increased prevalence in early age groups, as it may vary from 18.8% to 26.3% in Brazilian cohorts comprising children and adolescents [11][12][13] . Body fat (BF) distribution is as important as O/O.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados encontrados em nossa casuística apontam para uma forte correlação entre os indicadores avaliados (IMC, CC e RCEst), o que também tem sido descrito por outros autores 8,30 . Por mais que tenham apresentado uma forte correlação, o uso de mais de um indicador parece apontar informações adicionais, sobretudo no que diz respeito ao risco de comorbidades relacionadas ao excesso de peso quando associado também à adiposidade central.…”
Section: Discussionunclassified
“…O índice de massa corporal (IMC) tem sido o método antropométrico mais utilizado para avaliação do estado nutricional, por ser uma medida simples e de baixo custo e que tem apresentado uma boa concordância entre os indicadores de adiposidade no diagnóstico de sobrepeso e obesidade 8 e o risco de doença cardiovascular 9 . Apesar dessas vantagens, os inúmeros pontos de discriminação diagnóstica do IMC, embasados em estudos empíricos nacionais 10 ou internacionais 11,12 , têm dificultado, sobremaneira, a construção de uma base de referência que permita uma estimativa mais consistente da magnitude e evolução desse distúrbio nutricional.…”
Section: Introductionunclassified
“…Thus, these are two important methods for the diagnosis of overweight/obesity and of central obesity both in epidemiological studies and in the clinical practice 10,11 , because they are precise, reproducible, and easy to perform 12 .…”
mentioning
confidence: 99%